Novel detergent for whole organ tissue engineering. Issue 10 (17th June 2015) - Kawasaki, Takanori; Kirita, Yuhei; Kami, Daisuke; Kitani, Tomoya; Ozaki, Chisa; Itakura, Yoko; Toyoda, Masashi; Gojo, Satoshi
Abstract Whole organ tissue engineering for various organs, including the heart, lung, liver, and kidney, has demonstrated promising results for end‐stage organ failure. However, the sodium dodecyl sulfate (SDS)‐based protocol for standard decellularization has drawbacks such as clot formation in vascularized transplantation and poor cell engraftment in recellularization procedures. Preservation of the surface milieu of extracellular matrices (ECMs) might be crucial for organ generation based on decellularization/recellularization engineering. We examined a novel detergent, sodium lauryl ether sulfate (SLES), to determine whether it could overcome the drawbacks associated with SDS using rat heart and kidney. Both organs were perfused in an antegrade fashion with either SLES or SDS. Although immunohistochemistry for collagen I, IV, laminin, and fibronectin showed similar preservation in both detergents, morphological analysis using scanning electron microscopy and an assay of glycosaminoglycan content on ECMs showed that SLES‐treated tissues had better‐preserved ECMs than SDS‐treated tissues. Mesenteric transplantation revealed SLES did not induce significant inflammation, as opposed to SDS. Platelet adhesion to decellularized tissues was significantly reduced with SLES. Overall, SLES could replace older detergents such as SDS in the decellularization process for generation of transplantable recellularized organs. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3364–3373, 2015.